Mid-infrared laser spectroscopy for sensing applications - Chow, Travis Chin Hau (Nanyang Technological University, 2022)
Mid infrared lasers have been attractive for many applications including spectroscopy, imaging, gas sensing, chemical sensing and even military applications. This report introduces a simple quantum cascade laser setup for gas detection or food sensing. First, the knowledge fundamentals are introduced. Second, the system and experiment setups are explained, followed by the analyzation and summary of the experiment results. Lastly, the discussion on improvements needed and possible future improvements for the setup.